National health promotion and disease prevention objectives: full report, with commentary (Washington, D.C., 1991)
This book contains healthy people 200 and national health promotion and disease prevention objectives.
Keywords: Health promotion,Medicine, preventive,Nâng cao sức khỏe,Y học, phòng ngừa; Government policy,Government policy,Chính sách của chính phủ,Chính sách của chính phủ